Retrospective study of congenital anomalies in cattle from 2008 to 2020, necropsied at the Center for Teaching and Diagnosis of Bovine Diseases, UNAM, Mexico - Moctezuma, Kaylin L; Alva, Mario A Bedolla; Arjona-Jiménez, Guadalupe (Brazilian Journal of Veterinary Pathology, 2024)
From the files of the necropsy archive of the Center for Teaching and Diagnosis of Bovine Diseases (CEDEB), UNAM, a retrospective study of the cases of bovines sent to the post-mortem room was conducted, which covered a period of 13 years from 2008 to 2020, with the aim of identifying which are the main congenital diseases diagnosed in the post-mortem study. For the data analysis, the individual’s age, breed, and morphological diagnosis were considered. From 2008 to 2020, 2000 animals (100%) of which were divided into developmental stages: lactating calves, weaned calves, heifers, adults, and abortions; 40 (2%) of those animals were diagnosed with one or several developmental anomalies, the majority of cases were from lactating animals. The predominant congenital diseases were cardiovascular, locomotor, and gastrointestinal. From the group of congenital diseases of the cardiovascular system, they affected most stages of development, such as lactating calves, weaned calves, heifers, and adults.